Valid Cues for Auditory or Somatosensory Targets Affect Their Perception: A Signal Detection Approach. (February 2013) - Van Hulle, Lore; Van Damme, Stefaan; Crombez, Geert
We investigated the effects of focusing attention towards auditory or somatosensory stimuli on perceptual sensitivity and response bias using a signal detection task. Participants ( N = 44) performed an unspeeded detection task in which weak (individually calibrated) somatosensory or auditory stimuli were delivered. The focus of attention was manipulated by the presentation of a visual cue at the start of each trial. The visual cue consisted of the word "warmth" or the word "tone". This word cue was predictive of the corresponding target on two-thirds of the trials. As hypothesised, the results showed that cueing attention to a specific sensory modality resulted in a higher perceptual sensitivity for validly cued targets than for invalidly cued targets, as well as in a more liberal response criterion for reporting stimuli in the valid modality than in the invalid modality. The value of this experimental paradigm for investigating excessive attentional focus or hypervigilance in various non-clinical and clinical populations is discussed.